Gold-catalyzed access to pyrrolo- and (aryl)indolo-fused phenazines [data] - Rudolph, Matthias; Hüßler, Christopher; Dietl, Martin C.; Scherr, Matthias; Blaum, Immanuel E.; Stuntebeck, Hanno; Trogemann, Lea; Schmidt, Sophia; Kahle, Justin; Krämer, Petra; Rominger, Frank; Hashmi, A. Stephen K. (Universität, 2025)
Novel fused phenazines were synthesized through a combination of gold-catalyzed hydroamination and cascade cyclization reactions towards azaacenes. In total, 30 new compounds were synthesized and investigated with respect to their structural and optoelectronic properties. In solution, these targets exhibit strong green to red emission, with quantum yields of up to 60 %. The emission wavelength can be finely adjusted by the choice of solvent due to their solvatochromic behavior, as demonstrated with a representative example.